Reconstruction of the tongue and mouth floor with the myofascial vastus lateralis free flap after cancer ablation. Issue 8 (August 2016) - Wang, L.; Liu, K.; Shao, Z.; Shang, Z.-J.
Abstract: The current study was undertaken to evaluate a novel approach to tongue and mouth floor reconstruction using the myofascial vastus lateralis free flap (MVLF). The surgical techniques, benefits, complication rate, and the aesthetic and functional results are described. A series of six patients underwent functional tongue reconstruction between July 2013 and November 2014. The myofascial vastus lateralis flap was obtained as follows: the vastus lateralis muscle was exposed, the neurovascular pedicle was identified, and the myofascial flap was raised. Postoperatively, the neotongue appeared plump and was able to maintain palatal contact. Moreover, no obvious decrease in flap volume was observed during the follow-up period. Most patients experienced good tongue mobility. Further use of the MVLF should confirm whether the mucous membrane on the surface of the flap becomes part of the tongue mucosa in the true sense, whether and how well the patients will recover their sense of taste, and the degree to which quality of life is improved after nerve anastomosis. So far, it appears to be a suitable approach to tongue and mouth floor reconstruction.